The Analysis of Leading Plant Sector Commodities in North Konawe District - Nikoyan, Anas (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
The study aimed to determine the leading commodity in the plantation sector in North Konawe District. The study was conducted in North Konawe District in December 2019. The selection of the research object was carried out purposively with the consideration that North Konawe District is one of the regions in Southeast Sulawesi Province which makes the plantation sector as one of the sectors that have potential and plays an important role in improving regional economy. The study was conducted using a literature review method based on secondary data, namely data obtained from various sources such as the Central Statistics Agency, the Plantation Office, and relevant research results. The analysis of the data used was Location Quotient Analysis (LQ), Dynamic Location Quotient Analysis (DLQ), and Analysis of the Combination of LQ and DLQ. The results showed that the plantation sector commodities in North Konawe District were classified as superior, while those which not yet potential to be superior were coconut, oil palm, coffee, pepper, cashew, sago, candlenut, and nutmeg.